2019
DOI: 10.1007/s40620-019-00656-5
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of metabolic acidosis with sodium bicarbonate delays progression of chronic kidney disease: the UBI Study

Abstract: BackgroundMetabolic acidosis is associated with accelerated progression of chronic kidney disease (CKD). Whether treatment of metabolic acidosis with sodium bicarbonate improves kidney and patient survival in CKD is unclear.MethodsWe conducted a randomized (ratio 1:1). open-label, controlled trial (NCT number: NCT01640119. www.clinicaltrials.gov) to determine the effect in patients with CKD stage 3–5 of treatment of metabolic acidosis with sodium bicarbonate (SB) on creatinine doubling (primary endpoint), all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(126 citation statements)
references
References 34 publications
3
98
2
2
Order By: Relevance
“…The mean dose required to reach this serum bicarbonate concentration (some 3-4 mmol/L higher than in the usual care arm) was 6 g/day of sodium bicarbonate-much higher than used in the BiCARB trial. The UBI trial showed a significant reduction in the rate of progression of CKD, death and dialysis commencement in the bicarbonate arm compared to usual care [34]. Patients in this trial were slightly younger (mean age 67 years) and had considerably better renal function (mean eGFR of 36 mL/min/1.73 m 2 ), but the trial was not placebo-controlled or blinded.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 91%
“…The mean dose required to reach this serum bicarbonate concentration (some 3-4 mmol/L higher than in the usual care arm) was 6 g/day of sodium bicarbonate-much higher than used in the BiCARB trial. The UBI trial showed a significant reduction in the rate of progression of CKD, death and dialysis commencement in the bicarbonate arm compared to usual care [34]. Patients in this trial were slightly younger (mean age 67 years) and had considerably better renal function (mean eGFR of 36 mL/min/1.73 m 2 ), but the trial was not placebo-controlled or blinded.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 91%
“…Dietary interventions in patients with CKD and metabolic acidosis, comprising increased intake of fruits and vegetables or reduced animal protein intake, have been shown to be effective in raising serum bicarbonate and slowing kidney disease progression (Goraya et al, 2014;Garneata et al, 2016). Additionally, oral alkali supplementation (sodium bicarbonate, sodium citrate) in patients with CKD and metabolic acidosis has also been shown to increase serum bicarbonate and slow kidney disease progression (de Brito-Ashurst et al, 2009;Phisitkul et al, 2010;Di This article has not been copyedited and formatted. The final version may differ from this version.…”
Section: Introductionmentioning
confidence: 99%
“…JPET Fast Forward. Published on October 8, 2020 as DOI: 10.1124/jpet.120.000190 at ASPET Journals on October 31, 2020 jpet.aspetjournals.org Iorio et al, 2019;Dubey et al, 2020). These approaches reduce dietary acid intake or neutralize endogenous acid with oral bicarbonate but have the disadvantage of potentially increasing serum potassium (dietary approaches) or introducing significant sodium (oral alkali) in patients with CKD who are prone to hyperkalemia and sodium-sensitive comorbidities .…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not include or exclude participants based on blood pH. 7,8 Thus, blood pH may Related article, p. *** not ultimately influence decision making with regard to treatment. The utility of blood pH may be in its prognostic value, wherein hypobicarbonatemia accompanied by acidemia may signal a poorer prognosis than if blood pH were not low, presumably reflecting more substantial acid accumulation (Fig 1).…”
mentioning
confidence: 99%